Self-Organizing Architecture In Data Centers For Power Management - Jason, Sebagenzi; Suchithra, R (International Journal of Computer Sciences and Engineering, 2018)
The huge amount of data which can be stored and processed with the use of the internet has resulted in the capacity of data centers get bigger. This has resulted in the increase of the consumption of the power in data centers significantly and the management of power consumption in data centers has become essential. There are many techniques that have been proposed in that prospective. This paper highlights the need of managing the power in data centers, in order to reach the target of the efficiency of the power and observe several architectural techniques designed for its management of power. The detail of techniques is also given based on their behavior. The purpose of this paper is to provide intuition into the techniques to improve energy efficiency of data centers by using self-organizing architecture proposed and also to request the designers to continue producing solutions which can help for managing the dissipation of the power of data centers.